Knowledge, Attitude and Practices of Indigenous People Towards Non-Communicable Diseases In Bera, Malaysia: A Community Based Study - Abdullah, Fa’iza; A. Rahman, Nor Azlina; Kumaran, Viknaswaran; Fazam, Nurnisya; Wong, Chai Eng (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association of Malaysia, 2023)
Introduction: With the current trend of increasing noncommunicable diseases (NCDs) such as hypertension, diabetes and dyslipidemia worldwide and in Malaysia, a comprehensive study is essential to elucidate the local population's knowledge, attitude and practice (KAP) toward NCDs. Objective: e study investigated the KAP status towards NCDs and the association with sociodemographic background among Orang Asli adults of the Semelai subgroup in Central Pahang, Malaysia. Methods: A cross-sectional study was conducted among 251 Semelai adults in the Bera district, Pahang. Socio-demographic and KAP data were collected through face-to-face interviews and analysed using SPSS version 22.0. Continuous data were expressed descriptively as mean, median, and standard deviation. Bivariate analysis was performed to test the association between respondents’ socio-demographic factors and the KAP score. Results: Most of the respondents were females (57.4%), married (82.5%), completed primary school (75.3%), animism believers (83.3%), self-employed (75.3%) and earning less than RM1000 (87.6%). e age of the respondents ranged from 18 to 77 years old, with a mean (standard deviation) age of 41.1 (13.9). e prevalence of known type-2 diabetes mellitus (T2DM), hypertension and dyslipidemia were 9.6%, 20.7% and 8.8%, respectively. About 23.1% of respondents have a family history of chronic disease. Regarding KAP, only 12.7% demonstrated good knowledge while 35.5% depicted good practice in prevention and treatment. Nevertheless, more than half (59.8%) have a positive attitude towards chronic diseases. Higher household income and education levels were positively associated with higher KAP scores (p<0.001). Conclusion: Low-to-moderate percentage of Orang Asli in this study have good knowledge, attitudes, and practices towards NCD. Low levels of KAP are signicantly associated with poverty and poor education. Improving Orang Asli’s education and eradicating poverty may assist to improve their KAP towards healthiness, thereby enhancing their well-being and disease intervention.